Labor market effects of health promotion on human capital - Gottfried, Péter (International Journal of Engineering and Management Sciences, 2020)
Today, workplace health promotion is increasingly present, both domestically and internationally. In my research, I used literature analysis to show how workplace health promotion programs, including physical activity, how affect employee earning capacity and productivity. Human capital is a significant factor in productivity. Human capital can be defined, that the human inner, inseparable features and characteristics of a person to which is invested and, as a result, increases the productivity of the individual. Investments can include health spending (health promotion programs), costs of extra-curricular lessons and time to find the ideal job.I’ve been used secondary data collection during my research. In my research I have reviewed the source of literature on health promotion and physical activity primarily. After reviewing the literature, consequence of the research that investing in health, including investing in physical activity, it also contributes to improving health, as well as increasing life earnings and productivity at work.